Maternal mortality in the covid-19 pandemic: findings from a rapid systematic review. Issue Volume 14(2020-2021)Issue Supplement 1 (26th October 2021) - Calvert, Clara; John, Jeeva; Nzvere, Farirai P; Cresswell, Jenny A.; Fawcus, Sue; Fottrell, Edward; Say, Lale; Graham, Wendy J.
ABSTRACT: Background: The COVID-19 pandemic is having significant direct and associated effects on many health outcomes, including maternal mortality. As a useful marker of healthcare system functionality, trends in maternal mortality provide a lens to gauge impact and inform mitigation strategies. Objective: To report the findings of a rapid systematic review of studies on levels of maternal mortality before and during the COVID-19 pandemic. Methods: We systematically searched for studies on the 1st March 2021 in MEDLINE and Embase, with additional studies identified through MedRxiv and searches of key websites. We included studies that reported levels of mortality in pregnant and postpartum women in time-periods pre- and during the COVID-19 pandemic. The maternal mortality ratio was calculated for each study as well as the excess mortality. Results: The search yielded 3411 references, of which five studies were included in the review alongside two studies identified from grey literature searches. Five studies used data from national health information systems or death registries (Mexico, Peru, Uganda, South Africa, and Kenya), and two studies from India were record reviews from health facilities. There were increased levels of maternal mortality documented in all studies; however, there was only statistical evidence for a difference in maternal mortality in the COVID-19 era for four of these. Excess maternal mortality ranged from 8.5% in Kenya to 61.5% in Uganda. Conclusions: Measuring maternal mortality in pandemics presents many challenges, but also essential opportunities to understand and ameliorate adverse impact both for women and their newborns. Our systematic review shows a dearth of studies giving reliable information on levels of maternal mortality, and we call for increased and more systematic reporting of this largely preventable outcome. The findings help to highlight four measurement-related issues which are priorities for continuing research and development.